Identification of Sr genes in new common wheat sources of resistance to stem rust race Ug99 using molecular markers - O. A. Baranova; I. F. Lapochkina; A. V. Anisimova; N. R. Gajnullin; I. V. Iordanskaya; I. Yu. Makarova (Вавиловский журнал генетики и селекции)
The need for new donors of resistance to aggressive race Ug99 of Puccinia graminis Pers. f. sp. tritici Eriks. et Henn has arisen because the pest approaches the territory of Russian Federation. Identification of seventeen known Sr genes was performed with use of molecular markers in six sources of resistance to stem rust race Ug99. They included five common wheat lines and Donskaya Polukarlikovaya cv. The investigated accessions carried genetic material of alien species (Aegilops speltoides, Aе. triuncialis, Secale cereale). We used molecular markers associated with effective genes to race Ug99: Sr2, Sr22, Sr24, Sr25, Sr26, Sr32, Sr35, Sr36, Sr39, Sr40, Sr44, Sr47, and with genes that were ineffective but protected wheat cultivars against local pathogen populations: Sr9a, Sr15, Sr17, Sr19 and Sr31. On the grounds of the analysis of molecular markers the presence of two to seven known Sr genes was postulated in analyzed wheat lines :Sr2, Sr36, Sr39, Sr40, Sr44, Sr47 and Sr15 in line 113/00i-4; Sr22, Sr32, Sr44, Sr9a, Sr17 and Sr19 in line 119/4-06rw; Sr24, Sr36, Sr40, Sr47, Sr15, Sr17 and Sr31 in line GT 96/90; Sr22, Sr44, Sr32 and Sr15 in line 9/00w; Sr22 and Sr44 in line 141/97w. Genes Sr32 and Sr44 effective against Ug99 and ineffective genes Sr9a, Sr17 and Sr19 were identified in Donskaya Polukarlikovaya cv. The accessions studied may be recommended as donors of resistance to race Ug99 in wheat breeding programs.